PSIKOEDUKASI STRATEGI MENGATASI DAMPAK FOMO DAN MENINGKATKAN SELF-ESTEEM PADA PELAJAR SMA ISLAM AL-MAARIF SINGOSARI - Lisa Auliana; Laila Ni'matus Syarifah; Lintang Putri Kinanthi; Lakeisha Tabina Rahman (FIP UNIRA MALANG, 2026)
Adolescence is a phase when individuals focus on searching for their identity and increasing social interaction. Increased social interaction with peers makes adolescents very vulnerable to the phenomenon of Fear of Missing Out (FOMO). The Fear of Missing Out (FOMO) phenomenon has many negative effects, such as frequently checking social media for fear of missing out on trends, low self-esteem, and impulsive behavior. Fear of Missing Out (FOMO) also affects the mental health of adolescents, namely by lowering their self-esteem. Given the many impacts of FOMO on adolescents, intervention through psychoeducation is important. Psychoeducation aims to increase students' understanding of the impacts of FOMO and improve self-esteem in adolescents. The psychoeducation activity was carried out at Al-Maarif Islamic High School in Singosari in class XI MIPA 1. The psychoeducation activity began with a pretest using Google Forms, a presentation of material related to FOMO and self-esteem, followed by a Focus Group Discussion (FGD), an interactive activity in the form of a reflection session, and concluded with a posttest in the form of a case study. The results of this activity showed that the understanding of students in class XI MIPA 1 regarding FOMO and self-esteem had increased, as indicated by the fact that out of 28 students, 25 were able to answer the case study well and accurately, while 3 answered fairly well.